The Havana Peace Process: A Missed Opportunity for Ethnic Pluralism - Cabra- Salinas, Edgar Saúl (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper intends to advance in the theoretical analysis of pluralism, from the conceptions of Rawls, Habermas and Kymlicka, taking as reference the ethnic component incorporated in the Peace Agreement signed between the Colombian Government and the guerrillas of the Revolutionary Armed Forces of Colombia -FARC-EP- (by its acronym in Spanish) and the precarious participation of the indigenous communities in the decision-making regarding the territories and the ignorance of their rights, particularly that of prior consultation, despite the fact that they have suffered the serious consequences of the social and political conflict in the country.